Strategic Management Practices, Challenges, and Strategies: A Case of a State University - Mark Clessdy Cabangon Reyes (Fakultas Bisnis - Institut Bio Scientia International Indonesia, 2025)
This study unearthed current practices, challenges and strategies in strategic management, a case of a State University. Specifically, this study aimed to answer the following questions: (a) What are the current practices of strategic management in a state university? (b) What challenges do the participants encounter in strategic management; and (c) What are the strategies employed by the participants to overcome these challenges? This exploration utilized the qualitative approach, specifically utilizing the phenomenological methodology. A total of 7 participants accepted the invitation, providing the researcher a consent to conduct and record the interviews. Major results are as follows: A state university's present strategic management procedures demonstrate a thorough approach to developing, putting into practice, and assessing strategies. Qualitative responses from middle and upper management emphasize the significance of creating vision and mission statements, performing internal and external audits, and including stakeholders in the planning process when formulating a strategy. In terms of strategy implementation, the university emphasizes operationalizing strategies, tracking progress, aligning with objectives, distributing responsibilities, and providing support for implementation. Lastly, the university’s strategy evaluation framework incorporates performance measurement through annual reviews and key performance indicators (KPIs), alongside stakeholder feedback, ensuring a thorough assessment of strategies. Participants noted difficulties in aligning institutional goals with national and local standards, limited financial resources, stakeholder conflicts, and the complexities of conducting comprehensive external and internal audits. In sum, the generated themes on strategies employed by the participants to overcome the challenges in strategic management are as follows: collaboration and innovation, capacity building, continuous learning, stakeholder.